2020
DOI: 10.9758/cpn.2020.18.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity Indices as a Prognostic Factor for Remission in Schizophrenia

Abstract: Objective: Mismatch negativity (MMN) is known to be associated with neuro-cognition and functional outcomes. Remission and recovery rates are related to the neuro-cognition of patients with schizophrenia. The present study explored the relationship of MMN with remission in patients with schizophrenia. Methods: Forty patients with schizophrenia were recruited and divided into two groups, with or without remission, according to the Remission in Schizophrenia Working Group criteria (RSWGcr). Symptom severity (Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…However, other variables such as neurophysiological (MMN) parameters except for dMMN amplitude, various clinical variables (age, medication, illness duration, DUP, and PANSS score), and cognitive and social functions (BACS, mGAF, SCoRS, and JART IQ scores) did not contribute to the prediction. This was an unexpected finding because previous studies have demonstrated that predictors of treatment response and long-term outcome in schizophrenia included these factors (6,11), especially DUP (4,5). However, the present results may be partly consistent with our previous reports that changes in ERPs including MMN were observed prior to changes in neuropsychological test results (56,57).…”
Section: Discussionsupporting
confidence: 91%
“…However, other variables such as neurophysiological (MMN) parameters except for dMMN amplitude, various clinical variables (age, medication, illness duration, DUP, and PANSS score), and cognitive and social functions (BACS, mGAF, SCoRS, and JART IQ scores) did not contribute to the prediction. This was an unexpected finding because previous studies have demonstrated that predictors of treatment response and long-term outcome in schizophrenia included these factors (6,11), especially DUP (4,5). However, the present results may be partly consistent with our previous reports that changes in ERPs including MMN were observed prior to changes in neuropsychological test results (56,57).…”
Section: Discussionsupporting
confidence: 91%
“…P300 is not a unitary phenomenon, but it is composed of 2 functionally different subcomponents: an early component, the P3a, which usually peaks within a time window of 130–275 ms after the stimulus onset, that reflects an involuntary shift in attention toward a deviant stimulus; a later component, the P3b, observed within a time window of 275–600 ms after the stimulus, that reflects a conscious and controlled attentive process toward a stimulus and its task-relevance ( 60 ). Some studies explicitly differentiated P3a and P3b, analyzing one or both subcomponents in the same sample, while others referred more generally to P300 recordings.…”
Section: Resultsmentioning
confidence: 99%
“…A vast EEG literature has documented different abnormalities of neuronal activity in subjects with chronic SCZ, as compared to healthy controls (HCs) ( 29 , 33 , 43 49 ). In particular, several studies have consistently reported alterations in the activity of the whole spectrum of frequency bands ( 49 53 ), changes in MSs topography and/or other parameters ( 46 , 47 , 54 ) and a reduction of amplitude in ERPs, such as N100 ( 55 58 ), mismatch negativity (MMN) ( 59 , 60 ), and P300 ( 33 , 57 , 61 ). Furthermore, these alterations have been related to the severity of symptoms, as well as cognitive and functional impairment in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data were processed with a 0.1–100 Hz band-pass filter and sampled at 1000 Hz. The EEG acquisition procedure was described in our previous study 74 , 75 .…”
Section: Methodsmentioning
confidence: 99%